Exploring the multifaceted factors influencing overweight and obesity: a scoping review - Mohsen Jalilzadeh; Salime Goharinezhad (Frontiers in Public Health)
IntroductionObesity and overweight problems in public health have substantial impacts which affect the health status of individuals and community well-being and healthcare service provision worldwide. This scoping review aims to identify and classify factors from social, technological, environmental, economic and political domains which influence obesity and overweight conditions. The systematic analysis of determinants in this study generates usable information to guide public health intervention design and obesity epidemic management strategies.MethodsThe study utilized the ProQuest, ISI Web of Science, PubMed, and Scopus databases, and it also included grey literature in its analysis. The research objectives focused on identifying factors that contribute to overweight or obesity issues. The researchers used framework analysis to examine the qualitative data collected from these studies.ResultsThe synthesis incorporated 121 research studies which satisfied the established criteria. This comprised 98 studies from 46 different countries, 17 studies conducted at the international level, and 6 studies involving multiple countries. Eighty-two factors influencing overweight and obesity were identified as determinants and categorized into five main categories: sociocultural, economic, technological, environmental, and political. Most of the identified determinants belong to the socio-cultural category, which demonstrates their substantial impact on lifestyle and health behaviors.ConclusionThe implementation of public health prevention and intervention programs depends on complete knowledge of all factors that affect overweight and obesity rates. This issue needs a comprehensive approach which analyzes sociocultural aspects together with economic, technological, environmental, and political factors, as well as other policy goals within defined societal challenges. Effective solutions to resolve this situation depend on multi-sectoral collaboration to tackle obesity and promote health-enhancing factors for the entire community.